Surgical stress and cytoskeletal changes in lens epithelial cells following manual and femtosecond laser-assisted capsulotomy - Sükösd, Andrea Krisztina (Int J Ophthalmol, 2020)
AIM: To study the effect of mechanical stress on the cytoskeleton in lens epithelial cells following conventional phacoemulsification surgery (CPS) and femtosecond laser-assisted cataract surgery (FLACS). METHODS: The cytoskeleton of the epithelial cells of the anterior lens capsules (ALC) removed by CPS and FLACS was examined by immunohistochemistry. Expression of the intermediate filament, glial fibrillary acidic protein (GFAP), and glutamine synthetase (GS) immunoreactivity were detected. In order to map the actin network of cells, fluorescently labeled phalloidin was used. The samples were examined using confocal laser scanning microscopy. RESULTS: GFAP expression was visible in a larger number of the epithelial cells after CPS compared to FLACS. In CPS sample's epithelial cells, GFAP immunoreactivity indicated robust morphological change. Regarding the actin filaments, the presence of tubular elements connecting epithelial cells, regular actin pattern and marked cortical network after CPS were found. Following FLACS, the actin cytoskeleton of the epithelial cells remained densely structured, and the tubular elements were undetectable, however, the above-mentioned regular actin pattern and the marked cortical network were visible. CONCLUSION: The conventional removal of the ALC induces more robust changes of the cytoskeleton of the lens epithelial cells.